Gastroesophageal reflux disease at children: epidemiology, diagnostic criteria, prognosis - E. M. Mukhametova; S. I. Erdes (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
The aim of review. To present world literature data on epidemiology, features of course and diagnostics of gastroesophageal reflux disease (GERD) at children at different age.Original positions. Now the major attention is given by gastroenterologists and pediatrists to GERD at children, probability of its progression and development of complications in advanced age. Manifestations of GERD at children are different in various age-grades. At the first year of life of GERD manifests by regurgitation and vomiting. In most of the cases these symptoms are regarded to be physiological. However frequent regurgitation in this period of life is related to probability of further development of typical symptoms of GERD in these children. Along with growth, symptoms of GERD in children become more specific and similar to manifestations of disease at adults for whom the heartburn and acidic belching are considered as the most typical complaints. Basic methods of instrumental diagnostics of GERD and its complications at children, as well as at adults, include esophagogastroduodenoscopy and 24-hour esophageal and gastric рН-monitoring. However at children, there is no interrelation of clinical, endoscopic and рН-metrical changes severity.Conclusion. Above mentioned data testifies the absence of clear diagnostic criteria of GERD at children. For more exact diagnostics of GERD at pediatric age complex investigation of the child is required.